The “Tanzimat State” in the Ottoman Iraq: Tribes, Ideology/Shiism and taxation, 1830-1910 - Bektaş, Erhan. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2015., 2015)
This thesis, which handles the periods of the Tanzimat and Abdülhamid II, aims to examine the implementation of the Hamidian reform policies in the Iraqi province of the Ottoman Empire in the context of central government reactions towards the prevalence of Shiism in the nineteenth century. The focal points of this study are how the Shiite identity was perceived by the Ottoman state and the measures of the Ottoman Empire against the spread of Shiism in the Iraqi province. This thesis is based on Ottoman archival documents, and the narratives of contemporary observers and researchers about the Ottoman state policies against the spread of Shiism and the growing penetration of Britain and Iran throughout the Persian Gulf and Iraqi regions. It is also examines the relations between the tribes in Iraqi province and the Ottoman central state during the Tanzimat period. At the same time, this study aims to draw a wide-ranging panorama by the examination of the border policies of the Ottoman Empire, preventing the propagation of Shiism through the revival of Sunni educational institutions. Finally, the border policies of the Ottoman Empire in the nineteenth century in Iraq did not result in an achievement as the state desired.
Keywords: Shiites -- Iraq.